2003
DOI: 10.5254/1.3547772
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermal Aging on The Mechanical Properties of Natural Rubber

Abstract: The focus of this research was to investigate the effect of thermal degradation upon the mechanical properties of a natural rubber compound. We examined both the quasi-static and dynamic mechanical properties of a natural rubber vulcanizate which had been subjected to isothermal, anaerobic aging. The thermal aging was conducted between the temperatures of 80 °C and 120 °C for times ranging from 3 to 24 days. The effect of thermal degradation was measured using the changes in the crosslink distribution of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 2 publications
1
26
0
Order By: Relevance
“…The rubber chains were highly vulcanized, resulting in the decrease in the number of free chains, and the polysulfidic bonds could be broken into di-and mono-sulfidic ones as so-called maturation of sulfur crosslinks [11] and also confirmed by the work by South [9], indicating that the percentage of polysulfidic crosslinks in natural rubber chains decreased as the percentage of mono-sulfidic crosslinks increased with thermal aging. Furthermore, the oxygen linkages could be partially occurred, leading to higher crosslink density and greater hardness.…”
Section: Proposed Aging Modelmentioning
confidence: 64%
See 2 more Smart Citations
“…The rubber chains were highly vulcanized, resulting in the decrease in the number of free chains, and the polysulfidic bonds could be broken into di-and mono-sulfidic ones as so-called maturation of sulfur crosslinks [11] and also confirmed by the work by South [9], indicating that the percentage of polysulfidic crosslinks in natural rubber chains decreased as the percentage of mono-sulfidic crosslinks increased with thermal aging. Furthermore, the oxygen linkages could be partially occurred, leading to higher crosslink density and greater hardness.…”
Section: Proposed Aging Modelmentioning
confidence: 64%
“…Similarly, Ahlblad et al [26] also found that thermal oxidation of hydroxyl-terminated polybutadiene rubber increased crosslink density. It is likely that thermal decomposition of polysulfidic bonds may proceed faster than the oxidation of the rubber chains [9]. The model illustration is shown in Fig.…”
Section: Proposed Aging Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Ageing could indeed induce severe modifications of the mechanical properties both in terms of constitutive response [11], failure properties under monotonic tension [12], crack propagation [13] and duration life [14]. Nevertheless, relating the degradation mechanisms to the evolution of the mechanical properties is not an easy task because there are so many mechanisms at stake.…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…One of the principal reasons regarding permanent deformation of a rubber vulcanizate is change in crosslink density [3]. Thermal aging causes the crosslink density of a rubber vulcanizate to change [1,[4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%